STUDI PROPAGASI VEGETATIF TANAMAN OBAT KAYU ULES (Helicteres isoraLinn.) MELALUI STEK BATANG (A Study of Vegetative Propagation on Medicinal plant of Kayu Ules (Helicteres isora Linn.) Through Stem Cuttings) - Dani Pamungkas; Siswadi Siswadi; Gerhard Eli Sebastian Manurung (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2019)
Kayu Ules (Helicteres isora) is one medicinal plant species in which the fruits are utilized for manufacturing traditional medicine or jamu. Plant propagation of this species is one problem need to be investigated as only few studies conducted on this. This research was undertaken to investigate the ability of Kayu Ules propagated through stem cuttings. The experiment was designed with completely randomized design (CRD) using 2 main treatments which were the source of stem cutting materials including material from hard-wood, semi hard-wood and soft-wood stem. The second treatment was the use of commercial growth regulators, which were Atonik and Root-up. The result showed that cutting materials from soft-wood stem was not recommended due to very low survival. Meanwhile, the use of cutting material from semi hard-wood (24% with atonik, 12% with root-up and 8% with control) and hard-wood stem (36% with atonik, 24 % with root-up and 20 % with control) appeared potential to be used. This research recommended that there were six diameter classes of stem cutting showing ability to be propagated, which were diameter class I 5.86-7.61 mm (22.58%), II 7.62-9.37 mm (45.16%), III 9.38-11.33 mm (22.58%), IV 11.14-12.89 mm (3.23%), V 12.9-14.65 mm (3.23%), and VI 14.66-16.41 mm (3.23%).